Use the explicit formula an=4−3n to find the seventh term of the arithmetic sequence.

Responses

a7=−1

a7=1

a7=−17

a7=7

9 answers

To find the seventh term \( a_7 \) of the arithmetic sequence given by the explicit formula \( a_n = 4 - 3n \), we can substitute \( n = 7 \) into the formula.

\[ a_7 = 4 - 3(7) \]

Calculating this step-by-step:

  1. Calculate \( 3(7) = 21 \)

  2. Now substitute that back into the equation:
    \[ a_7 = 4 - 21 \]

  3. Finally, calculate \( 4 - 21 = -17 \)

Thus, the seventh term of the arithmetic sequence is

\[ \boxed{-17} \]

Given the recursive formula for the geometric sequence a1=5, an=2/5an−1, find the second term of the sequence.
Responses

a2=2/5

a2=2

a2=8/5

a2=5 2/5

Given the recursive formula for the geometric sequence \( a_1 = 5 \) and \( a_n = \frac{2}{5} a_{n-1} \), we need to find the second term \( a_2 \).

To find \( a_2 \), we substitute \( n = 2 \) into the recursive formula:

\[ a_2 = \frac{2}{5} a_1 \]

Since we already know that \( a_1 = 5 \):

\[ a_2 = \frac{2}{5} \times 5 \]

Calculating this:

\[ a_2 = \frac{2 \times 5}{5} = 2 \]

Thus, the second term of the sequence is

\[ \boxed{2} \]

Use the recursively defined geometric sequence a1=5/6, an=4an−1 and find the common ratio.
Responses

56

−23

103

4

In a geometric sequence, the common ratio \( r \) is defined as the factor by which we multiply one term to get the next term. Given the recursive formula for the geometric sequence:

  • \( a_1 = \frac{5}{6} \)
  • \( a_n = 4 a_{n-1} \)

we can see that to go from term \( a_{n-1} \) to term \( a_n \), we multiply by 4. Thus, the common ratio \( r \) is:

\[ r = 4 \]

Therefore, the common ratio of the sequence is

\[ \boxed{4} \]

Find the recursive formula for the arithmetic sequence 7, 5, 3, 1, . . .
Responses

a1=7, an=2an−1

a1=7, an=an−1−2

a1=7, an=−2an−1

a1=7, an=an−1+2

To find the recursive formula for the arithmetic sequence \( 7, 5, 3, 1, \ldots \), we first need to identify the first term and the common difference.

  1. The first term \( a_1 \) is given as \( 7 \).
  2. The common difference \( d \) between consecutive terms can be calculated as follows:
    • \( 5 - 7 = -2 \)
    • \( 3 - 5 = -2 \)
    • \( 1 - 3 = -2 \)

The common difference \( d \) is \( -2 \).

In a recursive formula for an arithmetic sequence, \( a_n \) can be defined in terms of the previous term as:

\[ a_n = a_{n-1} + d \]

Since \( d = -2 \), the formula becomes:

\[ a_n = a_{n-1} - 2 \]

Therefore, the recursive formula for the sequence is:

\[ a_1 = 7, \quad a_n = a_{n-1} - 2 \]

The correct option is:

\[ \boxed{a_1 = 7, , a_n = a_{n-1} - 2} \]

Which of the following correctly uses the explicit formula, An=1/4+(n−1)⋅1/2 , to find the 9th term of the described arithmetic sequence?
Responses

4 1/4

8 1/4

4 3/4

8 3/4

To find the 9th term of the arithmetic sequence using the explicit formula given by

\[ A_n = \frac{1}{4} + (n - 1) \cdot \frac{1}{2} \]

we will substitute \( n = 9 \) into the formula.

\[ A_9 = \frac{1}{4} + (9 - 1) \cdot \frac{1}{2} \]

Calculating step-by-step:

  1. Calculate \( 9 - 1 = 8 \).

  2. Now substitute that back into the equation: \[ A_9 = \frac{1}{4} + 8 \cdot \frac{1}{2} \]

  3. Calculate \( 8 \cdot \frac{1}{2} = 4 \).

  4. Now substitute that into the equation: \[ A_9 = \frac{1}{4} + 4 \]

  5. To add these, convert \( 4 \) to a fraction: \[ 4 = \frac{16}{4} \]

  6. Now add: \[ A_9 = \frac{1}{4} + \frac{16}{4} = \frac{17}{4} \]

Now, converting \( \frac{17}{4} \) to a mixed number gives us \( 4 \frac{1}{4} \).

Therefore, the 9th term of the arithmetic sequence is

\[ \boxed{4 \frac{1}{4}} \]